Why and How to Strengthen Indigenous Peoples' Food Systems With Examples From Two Unique Indigenous Communities - Kuhnlein, Harriet V.; Chotiboriboon, Sinee (Frontiers in Sustainable Food Systems, 2022)
Indigenous Peoples' food systems contain extensive and sophisticated knowledge that is often undocumented and underutilized in contemporary society that has increasingly poor nutrition and loss of food biodiversity. Indigenous Peoples in all global regions are among the most vulnerable to marginalization, food insecurity and chronic disease and will benefit greatly from strengthening their resource-rich food systems to make them more resilient and sustainable. It is in this spirit that we contribute to the databases of Indigenous Peoples' food system knowledge with information on unique traditional foods from the Nuxalk Nation in British Columbia, Canada, and the Pwo Karen People of Sanephong Community, Thailand. Several publications from these case studies originated from interdisciplinary mixed-method research, in part through the United Nations Food and Agriculture Organization. We highlight selected foods with nutrient data and various qualitative and quantitative methods used to identify and promote their use within these unique communities. Our intent is to stimulate complementary strengthening efforts among other traditional and Indigenous Peoples that will contribute to global intercultural food system evidence and advances.